CORPORATE SUSTAINABILITY REPORTING: A CONTENT ANALYSIS OF CSR REPORTING IN INDONESIA - Mulkhan, Unang (JURNAL PERSPEKTIF BISNIS, 2013)
This research explores how companies in Indonesia address on corporate sustainability reporting issue. In details, this research also attempts to explore some questions; how companies incorporate issues of stakeholder, social, economic, environment and generic in their CSR reports, and what the relative status of the Global Reporting Initiative (GRI) is. Secondary data was collected through an examination of companiesâ annual reports, sustainability reports, and CSR reports among Indonesian companies based on Indonesia Sustainability Reporting Award 2010. In order to answer the research questions, a combination of some frameworks, namely a framework to analyze and compare codes of conduct by Ans Kolk and Rob van Tulder (2001), a framework to analyze the implementation likelihood of sustainability report by Ans Kolk (2004), and GRI reporting guidelines (2006) were used to score and analyze of CSR reporting of those companies. This findings show that ten companies in ISRA 2010 report stakeholder issues and their achievements in conducting stakeholder engagement. Moreover, they take into account their stakeholders in their CSR reports. Furthermore, in terms of CSR reporting guidelines, CSR reporting standards are needed as guidelines for companies to produce CSR reporting. In some extent CSR reporting standards allow authorities to transparently and effectively measure and assess of CSR activities. Â Key words: Corporate sustainability reporting, stakeholders, CSR, Global Reporting Initiative (GRI).